Analisis Penerapan Pembelajaran Kreatif dalam Mata Pelajaran IPAS di SD Negeri 104203 Bandar Khalifah - Ratno, Suyit; Nur Hidayani Zahra; Puspita Br Damanik, Marsela; Gregoria Purba, Laurencia; Izza Marpaung, Shofiatul; Fanita Sihombing, Enjel; Ramadani Harahap, Bintang; Hasibuan, Safaruddin (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to analyze the implementation of creative learning in the subject of Science and Social Studies (IPAS) at SD Negeri 104203 Bandar Khalifah. The research uses a descriptive qualitative method, with data collection techniques including questionnaires for students, interviews with teachers, and observation of student interactions in the classroom. The results show that 80% of students feel more interested and motivated in learning when creative methods such as games, group discussions, and the use of visual aids are applied. Teachers also stated that the implementation of creative learning enhances students' understanding of the material, although challenges related to limited teaching resources and preparation time were encountered. Creative learning has been shown to increase student engagement and understanding, as well as facilitate more meaningful learning. Therefore, it is recommended that schools provide more support in terms of facilities and training for teachers to optimize the implementation of creative learning methods in the classroom.